Os caminhos para a construção da escola inclusiva:a relação entre a gestão escolar e o processo de inclusão. - Tezani, Thaís Cristina Rodrigues (2004)
The research has as fear the relation between school administration and the students inclusion process with special educational needs in the regular teaching, aiming at the construction of an inclusive school. It accomplished a qualitative research: an ethnographical kind comparative study between two public schools of an average postage city, of the interior of São Paulo s State, being a municipal net school and other of the teaching state net, guiding by the research matter: Which the actions school administration contribution for the students inclusion process with special needs in the regular teaching, guaranteeing, thus, the inclusive school construction . To the knowledge that the students with special educational needs have been frequenting common classes, it does necessary to study the school administration ahead of this reality, or be, your posture, conceptions and actions. The research goal is to describe the school administration actions in front of the student s inclusion process with special educational needs in the regular teaching. They recovered the paradigms that guiding the inclusion historical process and her philosophical dimensions, relating the proposal from official documents to the educational reality. They compare the actions and the schools school administration relations in the student s inclusion processes with special educational needs in the regular teaching. Checked itself how same, belonging to public school universe, studied schools follow proposed and accomplish distinct practices; it highlights that the posture assumed by the school administration influence in the everyday pedagogical practice and that parents' involvement and teachers' implication are determinate factors in the inclusive school construction.